Analysis of Subject Material and Material Presentation of 7th Grade Mathematics Books Viewed from Mathematics Learning Objectives - Maharani, Anindya Gita; Asikin, Mohammad; Dwidayati, Nurkaromah (Unnes Journal of Mathematics Education, 2017)
Penelitian ini bertujuan untuk mengetahui bagaimanakah kesesuaian materi dan penyajian buku pelajaran yang diterbikan oleh Erlangga ditinjau dari tujuan pembelajaran Matematika. Objek penelitian ini adalah buku teks pelajaran Matematika SMP yang digunakan di sekolah yaitu Matematika SMP kurikulum 2013 kelas VII semester II karangan M.Cholik Adinawan dan Sugijono yang diterbitkan oleh Erlangga tahun 2013. Buku Siswa terbitan Depdiknas tahun 2014 digunakan sebagai data pembanding. Data diperoleh dengan metode dokumentasi dan observasi. Analisis data yang digunakan adalah kajian isi melalui penskoran dengan menelah dan membandingkan kesesuaian materi dan penyajian buku teks ditinjau dari tujuan pembelajaran Matematika. Hasil penelitian menunjukkan bahwa: (1) Materi pada buku teks pelajaran Matematika SMP kelas VII terbitan Erlangga yang digunakan dalam kegiatan belajar mengajar di sekolah-sekolah di Kabupaten Pacitan secara umum sudah sesuai dengan tujuan pembelajaran Matematika. (2) Penyajian pada buku teks pelajaran Matematika SMP kelas VII terbitan Erlangga yang digunakan dalam kegiatan belajar mengajar di sekolah-sekolah di Kabupaten Pacitan secara umum sudah sesuai dengan tujuan pembelajaran Matematika. The purpose of this research is to determine how the suitability of the material and the presentation of textbooks published by Erlangga terms of learning objectives Mathematics. The object of this research is a mathematics textbooks used in junior high school curriculum 2013 is class VII 2013 second semester essay M.Cholik Adinawan and Sugijono published by Erlangga 2013. Student Book published by the National Education Ministry in 2014 was used as comparative data. Data obtained by the method of documentation and observation. Analysis of the data used is the study of the contents through the scoring with a predict and compare the suitability of the material and the presentation of textbooks in terms of learning objectives Mathematics. The results showed that: (1) The material in textbooks of Mathematics junior class VII Erlangga publications used in teaching and learning activities in schools in Pacitan in general are in accordance with the purpose of learning mathematics. (2) Presentation of the textbooks of Mathematics junior class VII Erlangga publications used in teaching and learning activities in schools in Pacitan in general are in accordance with the purpose of learning mathematics.